2022
DOI: 10.1007/s11255-022-03439-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy and risk factors of surgical treatment of recurrent UPJO in adults

Abstract: Background To compare the efficacy of secondary pyeloplasty and balloon dilation and to analyze the risk factors for secondary surgical failure in patients with recurrent uretero-pelvic junction obstruction (UPJO). Methods We retrospectively analyzed 65 patients with recurrent UPJO who underwent secondary surgery between September 2011 and March 2019, of whom 33 had complete baseline data and follow-up data. General clinical information, perioperative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The results of regression analysis conducted by Li [ 13 ] indicate that the length of the stenosis does not significantly influence the postoperative outcome. However, several studies [ 10 , 19 , 20 ] have reported that an excessively long stenosis (> 2 cm) is likely to result in poor postoperative recovery. Our logistic regression analysis revealed that the length of the stenosis segment is an independent risk factor for postoperative recurrence of stenosis (OR = 0.025, P = 0.011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of regression analysis conducted by Li [ 13 ] indicate that the length of the stenosis does not significantly influence the postoperative outcome. However, several studies [ 10 , 19 , 20 ] have reported that an excessively long stenosis (> 2 cm) is likely to result in poor postoperative recovery. Our logistic regression analysis revealed that the length of the stenosis segment is an independent risk factor for postoperative recurrence of stenosis (OR = 0.025, P = 0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advancements in technology and increased expertise, the success rate of pyeloplasty continues to improve. However, it is observed that approximately 2.5–10% of patients experience relapse after the initial operation [ 10 ]. Moreover, it is important to note that the recurrence rate of actual surgery may be higher due to insufficient follow-up time [ 11 ].…”
Section: Introductionmentioning
confidence: 99%